1995
DOI: 10.1002/j.1460-2075.1995.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for the cystic fibrosis delta F508 mutation.

Abstract: Most cystic fibrosis (CF) patients produce a mutant form (delta F508) of the cystic fibrosis transmembrane conductance regulator (CFTR), which is not properly processed in normal cells but is active as a chloride channel in several experimental systems. We used a double homologous recombination (‘Hit and Run’) procedure to generate a mouse model for the delta F508 mutation. Targeted embryonic stem (ES) cells (Hit clones) were found; of these either 80 or 20% of the clones had lost the delta F508 mutation, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
224
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(236 citation statements)
references
References 46 publications
(52 reference statements)
8
224
1
2
Order By: Relevance
“…7). A significant level of CFTR⌬F508 chloride channel activity and a detectable level of mature protein have been observed for the homozygous ⌬F508 CF mouse (65)(66)(67)(68). Our results suggest that the T539 could contribute to the attenuated defect caused by the ⌬F508 mutation in the murine CFTR.…”
Section: Discussionmentioning
confidence: 68%
“…7). A significant level of CFTR⌬F508 chloride channel activity and a detectable level of mature protein have been observed for the homozygous ⌬F508 CF mouse (65)(66)(67)(68). Our results suggest that the T539 could contribute to the attenuated defect caused by the ⌬F508 mutation in the murine CFTR.…”
Section: Discussionmentioning
confidence: 68%
“…However, ⌬F508-CFTR can function as a cAMP-regulated chloride channel, both in the plasma membrane and intracellularly (27). Previous studies demonstrated a residual chloride permeability in intestine and gallbladder of the Cftr ⌬F/⌬F mice used here (24), and the electrolyte and water handling is preserved in the PT of Cftr tm2cam ⌬F508…”
Section: Studies In Clcn5mentioning
confidence: 67%
“…These data suggest that in Cftr Ϫ/Ϫ mice, the complete loss of CFTR induces a significant decrease in the membrane stability and increased urinary excretion of cubilin, leading to a defective apical receptor-mediated endocytosis in PT cells, with urinary loss of LMW ligands (␤ 2 -microglobulin, CC16, and transferrin). This phenotype is observed less consistently in Cftr ⌬F/⌬F mice, which may be explained by a variable residual expression and/or functionality of the mutated ⌬F508-CFTR in the Cftr ⌬F/⌬F kidneys (24,33).…”
Section: Evaluation and Characterization Of Pt Apical Endocytosis In mentioning
confidence: 93%
“…34 Therefore, we aimed at translating these findings in vivo, into a mouse model of CF. For this, we took advantage of mice homozygous for the ΔF508-CFTR mutation in the 129/FVB outbred background (Cftrtm1EUR, F508del, FVB/129) (Cftr F508del ), an established animal model of CF, [46][47][48] that shows constitutive lung inflammation. 7,48 First, Cftr F508del mice were transduced intranasally with pLKO.1-CMV-tGFP lentiviral vectors expressing mouse shRNA specific for Sqstm1 or no target sequence (control shRNA) (n = 5 for each group of treatment) ( Fig.…”
Section: Resultsmentioning
confidence: 99%